Pharyngeal electrical stimulation to treat dysphagia in acute stroke: learnings from cases in the PhEED clinical trial - Harvey, Richard L.; Smith, Richard; Bathula, Rajaram; Everton, Lisa; Rup, Nicole; Saver, Jeff; Martin-Harris, Bonnie; Dziewas, Rainer; Mistry, Satish; Hamdy, Shaheen; Bath, Philip (Journal of rehabilitation medicine, 2025)
Objective: To assess the efficacy of pharyngeal electrical stimulation in improving dysphagia post-stroke. Design: A randomized, sham-controlled, blinded multicentre clinical trial. Subjects/Patients: Seventeen patients with acute ischaemic or haemorrhagic stroke experiencing dysphagia, indicated by a penetration aspiration scale score of 4–8 on videofluoroscopy. Methods: Sites enrolled 3 open-label roll-in participants and then randomized subsequent participants to either stimulation or sham treatment. Study interventions were delivered for 10 min daily over 3 consecutive days. Prior to data lock the primary outcome was modified to the change in dysphagia severity rating scale from pre-treatment to end of follow-up period. Secondary outcomes included penetration-aspiration scale score assessed via videofluoroscopy 48 h after final treatment and functional oral intake scale, measured at 7, 14, and 83 days post-randomization. Results: The trial was halted early due to low recruitment, with 15 participants receiving active stimulation and 2 receiving sham treatment. Active stimulation significantly reduced dysphagia severity at day 83 (difference: –4, p = 0.027). Improvements were observed in diet and supervision subscales, and functional oral intake scores. Of those treated, 67% were discharged home, with no serious adverse events attributable to the intervention noted in either group. Conclusion: Pharyngeal electrical stimulation was safe and associated with reduced dysphagia severity in stroke patients, warranting further validation in larger studies.